Clinical Manifestations of Different Histological Variants of Breast Carcinoma (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Introduction: The article conducted a retrospective analysis of medical histories and outpatient records of 1650 patients with breast cancer. An increase in the ability to metastasize has been established in poorly differentiated tumors compared to more mature forms. At the same time, the morphological aspect of metastasis in breast cancer has not been sufficiently studied, and studies devoted to this issue are few. Objective: To determine the survival prognosis depending on the histological type of breast cancer. Materials and methods: The study involved personal observations of patients, analysis of medical histories and outpatient records of patients treated at the Samarkand branch of the Russian National Medical Research and Medical Center from 2017 to 2022. During this time, 1650 patients with primary breast cancer were treated. Results: Depending on the stage of the process for Paget's breast cancer, patients were distributed as follows: I T 1, 2 N 0 M 0 y 6, II a T 2 N 0 M 0 y 13, II B, T 2 N 1 M 0 -y 5, III a T 3 N 0 M 0 y 4, III B, T 1,2,3 N 1,2 M 0 y 6. During a clinical examination of patients, the tumors had a lumpy surface and a dense consistency; 2 patients had dense, enlarged axillary lymph nodes. 7 patients had I - II a, T 2 N 0 M 0 stage of the process, 2 - III b, T 2-3 N 1-2 M 0 . The frequency of metastasis was 16.5%, information on 5-year survival is available for 2 patients, for the rest the duration of observation of patients continues. Conclusion: The most common histological form (50%) was Paget's cancer , characterized by a slow course, high 3 and 5 year survival of patients with locally advanced processes.